British Society of Gastroenterology position statement on serrated polyps in the colon and rectum. Issue 7 (27th April 2017) - East, James E; Atkin, Wendy S; Bateman, Adrian C; Clark, Susan K; Dolwani, Sunil; Ket, Shara N; Leedham, Simon J; Phull, Perminder S; Rutter, Matt D; Shepherd, Neil A; Tomlinson, Ian; Rees, Colin J
Abstract : Serrated polyps have been recognised in the last decade as important premalignant lesions accounting for between 15% and 30% of colorectal cancers. There is therefore a clinical need for guidance on how to manage these lesions; however, the evidence base is limited. A working group was commission by the British Society of Gastroenterology (BSG) Endoscopy section to review the available evidence and develop a position statement to provide clinical guidance until the evidence becomes available to support a formal guideline. The scope of the position statement was wide-ranging and included: evidence that serrated lesions have premalignant potential; detection and resection of serrated lesions; surveillance strategies after detection of serrated lesions; special situations—serrated polyposis syndrome (including surgery) and serrated lesions in colitis; education, audit and benchmarks and research questions. Statements on these issues were proposed where the evidence was deemed sufficient, and re-evaluated modified via a Delphi process until >80% agreement was reached. The Grading of Recommendations, Assessment, Development and Evaluations (GRADE) tool was used to assess the strength of evidence and strength of recommendation for finalised statements. Key recommendation : we suggest that until further evidence on the efficacy or otherwise of surveillance are published, patients with sessile serrated lesions (SSLs) that appear associated with a higher risk of future neoplasia or colorectal cancer (SSLs ≥10 mm or serrated lesions harbouring dysplasia including traditional serrated adenomas) should be offered a one-off colonoscopic surveillance examination at 3 years ( weak recommendation, low quality evidence, 90% agreement ).